Model Strategi Agribisnis Pisang Cavendish melalui Pendekatan Analisis SWOT di Sumatera Selatan Indonesia - fifian permata sari; Munajat . (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
The purpose of scientific work is to identify internal-external factors and recommended strategies for increasing Cavendish banana production in South Sumatra Province. The research was conducted in Jayapura District as the center of East Cavendish OKU banana production in March 2022. The sampling method used an unbalanced layered random method. Based on several related articles about Cavendish bananas, there are no articles that discuss strategies to increase Cavendish banana production using the SWOT analysis in Jayapura District, OKU Timur Regency. The results of the analysis show that the recommended strategies for increasing Cavendish banana production are strategies to increase the role of local governments as facilitators and price stabilization, partnership patterns with the private sector in terms of marketing Cavendish bananas, the need for technology utilization starting from input, process and output, intensive development of Department of Food Crops and Horticulture, and human resource development through Cavendish banana cultivation assistance. The conclusion of the study shows that it is necessary to implement strategies that can be recommended to increase Cavendish banana production, including the need for partnerships for Cavendish banana farmers and continuing to increase production standards so that East OKU Cavendish bananas can compete with imported Cavendish bananas.